Трематоды семейства Leucochloridiidae от воробьиных птиц Украины - Искова, Н.И. (Вестник зоологии, 1979)
The paper deals with the result of studies of Leucochloridiidae from Passeriformes investigated during 1964-1975 in different regions of the Ukraine. In all 11 species of Leucochlodiidae belonging to 3 genera are found. The descriptions and drawing are given for trematods species new for the fauna and the characteristic of all the species recorded in the Ukraine is presented.